Universities and secondary schools teaming up for a different entrepreneurship education: barriers, enablers, and outcomes of an open and collaborative process to co-design entrepreneurial competences developing experiential learning activities - Bitetti, Leandro; Huber, Andrea (Piccola Impresa / Small Business, 2023)
Purpose. This study explores the collaboration between universities and secondary schools in co-designing experiential learning activities for fostering entrepreneurial competences applying the EU Entrepreneurship Competence Framework. Methodology. Participatory action research involved sixty secondary school teachers from Italy and Switzerland. Findings. The study reveals barriers (lack of strategy, collaboration ecosystem, and competence monitoring), enablers (active tutoring, shared language, and digital technologies), and outcomes (teacher, learner, and bridging school-job gap). Practical and social implications. This study contributes a process framework for collaborative innovation between universities and secondary schools, informing the design of effective entrepreneurship education programs. Originality. The study is among the first to adopt a collaborative rather than a complimentary view of universities and secondary schools in the development of entrepreneurship education.